Of mice and humans through the looking glass: "reflections" on epigenetics of lipid metabolism. (April 2017) - Longo, Raffaella; Ferrari, Alessandra; Zocchi, Monica; Crestani, Maurizio
Abstract: Over the past decade, epigenetics has emerged as a new layer of regulation of gene expression. Several investigations demonstrated that nutrition and lifestyle regulate lipid metabolism by influencing epigenomic remodeling. Studies on animal models highlighted the role of epigenome modifiers in specific metabolic contexts and established clear links between dysregulation of epigenetic mechanisms and metabolic dysfunction. The relevance of findings in animal models has been translated to humans, as epigenome-wide association studies (EWAS) deeply investigated the relationship between lifestyle and epigenetics in human populations. In this review, we will provide an outlook of recent studies addressing the link between epigenetics and lipid metabolism, by comparing results obtained in animal models and in human subjects.